PEMANFAATAN CHATGPT SEBAGAI ASISTEN DALAM PROSES KREATIF SASTRA INDONESIA - Nur, Sajidah (Jurnal Cerdik: Jurnal Pendidikan dan Pengajaran, 2024)
Artificial intelligence is used massively in scientific writing and has been widely studied from various aspects. However, there are still few studies that examine the use of artificial intelligence in the creative process of Indonesian literature. This study is here to fill this gap by focusing on the use of artificial intelligence in the form of ChatGPT in the creative writing process of literature. The method used to process the research data is a qualitative method. The data source for this study was one informant who is a short story writer and poetry writer who uses ChatGPT in his creative writing process. Data collection was carried out through semi-structured in-depth interviews. The research data is in the form of interview transcripts analyzed using a flow model. The results of this study indicate that literary writers use ChatGPT at the exploration and processing stages of ideas and finalizing the written manuscript. Meanwhile, the writing stage is done independently. This implies that ChatGPT acts as an assistant in the creative process. Based on the author's experience, ChatGPT has advantages and disadvantages as an assistant in the creative process. The conclusion that can be put forward is that ChatGPT can be an assistant that supports the creativity and productivity of writers. However, when writing a script, literary writers tend to work independently to realize ideas in written form while maintaining their characteristics, writing style, story context, and emotional nuances.